Smart Material-Actuated Flexible Tendon-Based Snake Robot. (17th May 2016) - Ahmed, Mohiuddin; Billah, Md. Masum
A flexible snake robot has better navigation ability compare with the existing electrical motor-based rigid snake robot, due to its excellent bending capability during navigation inside a narrow maze. This paper discusses the modelling, simulation and experiment of a flexible snake robot. The modelling consists of the kinematic analysis and the dynamic analysis of the snake robot. A platform based on the Incompletely Restrained Positioning Mechanism (IRPM) is proposed, which uses the external force provided by a compliant flexible beam in each of the actuators. The compliant central column allows the configuration to achieve three degrees of freedom (3DOFs) with three tendons. The proposed flexible snake robot has been built using smart material, such as electroactive polymers (EAPs), which can be activated by applying power to it. Finally, the physical prototype of the snake robot has been built. An experiment has been performed in order to justify the proposed model.